Knowledge for Sale: Norwegian Encyclopaedias in the Marketplace - Siv Frøydis Berg; Tore Rem (Culture Unbound: Journal of Current Cultural Research, 2014)
Encyclopedias present and contain knowledge, but historically they have also been commercial commodities, produced for sale. In this article, we study the self-presentations of a selection of Norwegian encyclopedias, as these are expressed in the form of commercial images, advertising texts and slogans. We thus present a brief but detailed study of what might be called a number of paratextual matters associated with 20th-century Norwegian encyclopedias, with the aim of identifying the most significant or recurring topoi in the material. Our analysis shows that claims about speed and modernization are among the most conspicuous ingredients in these self-presentations, claims which, we argue, feed into a particular logic of a particular version of 20th-century modernity. The article begins with an analysis of the commercially successful Konversationslexicon, the first Norwegian encyclopedia, published in 1906 and for a long time market leader of the bourgeois tradition. The Konversationslexicon was produced with the explicit aim of providing a source of conversation for the educated classes, a new and expanding group of readers. We also show how the publisher Aschehoug went on to strengthen its own position in this market through a sophisticated process of differentiation. Seen as a contrast to these market leaders, we explore the Norwegian tradition of counter-encyclopaedias, with the radical PaxLeksikon as our main example. This encyclopaedia came into existence as a result of a strong ideological motivation and was run by left-wing idealists. Nevertheless, and perhaps inevitably, it ended up situating itself within the same market mechanisms and the same commercial logic as the bourgeois encyclopaedias. The article ends by a brief consideration of the change from commercial print encyclopaedias to internet-based encyclopaedias, and of the new challenges this poses in a small nation, rhetorically and in the struggle for funding.